Proceedings of the Twenty-Fourth ACM Symposium on Operating Systems Principles 2013
DOI: 10.1145/2517349.2522722
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of Facebook photo caching

Abstract: This paper examines the workload of Facebook's photoserving stack and the effectiveness of the many layers of caching it employs. Facebook's image-management infrastructure is complex and geographically distributed. It includes browser caches on end-user systems, Edge Caches at~20 PoPs, an Origin Cache, and for some kinds of images, additional caching via Akamai. The underlying image storage layer is widely distributed, and includes multiple data centers.We instrumented every Facebook-controlled layer of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(86 citation statements)
references
References 19 publications
1
85
0
Order By: Relevance
“…Once the hot object is detected, its replica is stored by the frontend cache, which can then serve all traffic flowing through it, via its local copy of the item and without burden on other servers. Studies show that even small front-end caches can substantially alleviate skewed object-access workload [5,7].…”
Section: Current Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the hot object is detected, its replica is stored by the frontend cache, which can then serve all traffic flowing through it, via its local copy of the item and without burden on other servers. Studies show that even small front-end caches can substantially alleviate skewed object-access workload [5,7].…”
Section: Current Techniquesmentioning
confidence: 99%
“…Our traces, therefore, are focused on load imbalance after caches higher up in the hierarchy have already been applied [7]. Moreover, our earlier analysis showed that after a layer of front-end caches, the popularities of objects are no longer a significant factor in Tao's load-imbalance.…”
Section: Current Techniquesmentioning
confidence: 99%
“…We found that SQLite and its journal files are responsible for approximately 90% of the write I/Orequests in both Facebook and Twitter applications. The reason for such high number of write I/O requests to the local storage is because Facebook and Twitter cache the timeline records in their SQLite table, which is common approach in modern SNS applications to improve the processing speed and to reduce the latency for user requests [30]. We also found that resources (.dat and .xml) and executable files are responsible for about 60% of the read I/O requests.…”
Section: I/o Characterization Of Android Applications With Mostmentioning
confidence: 91%
“…where p global [c] is the proportion of views in country c. UGC providers typically rely on multiple layers of caches (within browsers, at Internet Points-of-Presence, within datacenters), in addition to their primary storage system [21]. In our model, we aggregate all these caches in one single layer located in each country, set to an LRU eviction policy.…”
Section: A System Modelmentioning
confidence: 99%